The use of the dialogue and speeches in al-Tabari's account of the Battle of Siffin - Adair, Yolanda (AUC Knowledge Fountain, 2012)
Al-Ṭabarī compiled extensive historical accounts which include those regarding the Battle of Ṣiffīn. He reported the details of this battle in his compilation by using speeches and dialogues as a means of relaying the account to his audience. This thesis analyzes some of the speeches and dialogues that are presented in al-Ṭabarī’s historical account of the Battle of Ṣiffīn. The analysis is done for the purpose of determining the reasons for and effectiveness of this particular method of presentation. In order to perform this analysis, several factors were considered. The process by which early Arabic historiography in general came to exist was one of the primary factors that was considered. A second factor was to determine what scholars have said concerning the methodology that was utilized. Furthermore, other factors that were considered include what were the sources that were used in al-Ṭabarī’s compilation of the events and what scholars have determined concerning the reliability of those sources. Finally, how speeches and dialogues have been used by other historians in order to present both early Arabic and non-Arabic historical accounts, and how they compare to the presentation of this account were additional factors for consideration. Upon analyzing these and other factors, an analysis of the text was performed in order to review the methodology that was used by al-Ṭabarī in reporting this battle. In essence, these accounts which began as oral stories, continued to be passed down from the time of the event until the time of compilation. The analysis determined that he used the information as he received it directly from his sources, which used the story-telling characteristic that it originated with in order to compile his historical accounts. It was also determined that this methodology was effective in presenting the audience with an informative and entertaining narrative of the Battle of Ṣiffīn, because the information and details regarding the battle are given in an entertaining way through the use of the speeches and dialogues.